Proceedings of the Forty-Eighth Annual ACM Symposium on Theory of Computing 2016
DOI: 10.1145/2897518.2897536
|View full text |Cite
|
Sign up to set email alerts
|

The computational power of optimization in online learning

Abstract: We consider the fundamental problem of prediction with expert advice where the experts are "optimizable": there is a black-box optimization oracle that can be used to compute, in constant time, the leading expert in retrospect at any point in time. In this setting, we give a novel online algorithm that attains vanishing regret with respect to N experts in total O( √ N ) computation time. We also give a lower bound showing that this running time cannot be improved (up to log factors) in the oracle model, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 45 publications
1
71
1
Order By: Relevance
“…We show that any private pERM can be efficiently used as a no-regret learning algorithm with regret guarantees that depend on the scale of the perturbations it uses. This allows us to reduce to a lower bound on the running time of oracle-efficient online learning algorithms due to Hazan and Koren [HK16]. The result is that there exist finite classes of queries Q such that any oracle-efficient differentially private pERM algorithm must introduce perturbations that are polynomially large in the size of |Q|, whereas any such class is information-theoretically privately learnable with error that scales only with log |Q|.…”
Section: A Barrier Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We show that any private pERM can be efficiently used as a no-regret learning algorithm with regret guarantees that depend on the scale of the perturbations it uses. This allows us to reduce to a lower bound on the running time of oracle-efficient online learning algorithms due to Hazan and Koren [HK16]. The result is that there exist finite classes of queries Q such that any oracle-efficient differentially private pERM algorithm must introduce perturbations that are polynomially large in the size of |Q|, whereas any such class is information-theoretically privately learnable with error that scales only with log |Q|.…”
Section: A Barrier Resultsmentioning
confidence: 99%
“…We wish to exploit a lower bound on the running time of oracle efficient online learners over arbitrary sets Q due to Hazan and Koren [HK16]:…”
Section: Oracle-efficient No-regret Learning Algorithms Are Subject Tmentioning
confidence: 99%
See 2 more Smart Citations
“…As we show, when certain structural properties hold, the augmented history is of polynomial size even when the learner's action space is exponential, yielding oracle-efficient learning. Our results make significant progress on an open problem raised by Hazan and Koren [27], who showed that oracle-efficient algorithms do not exist in general [26] and asked whether one can identify properties under which oracle-efficient online learning may be possible.Our second main contribution is the introduction of a new adversarial online auction-design framework for revenue maximization and the application of our oracle-efficient learning results to the adaptive design of auctions. In our framework, a seller repeatedly sells an item or set of items to a population of buyers by adaptively selecting auctions from a fixed target class.…”
mentioning
confidence: 93%